Inflammatory markers in prepubertal children and their associations with abdominal fat - Letícia G. de Queiroz; Paulo F. Collett-Solberg; Maria das Graças C. de Souza; Nádia Cristina P. Rodrigues; Alexandra M. Monteiro; Cristiane de S. Mendes; Fernanda M. Gazolla; Cecília L. de Oliveira; Eliete Bouskela; Maria Cristina C. Kuschnir; Isabel R. Madeira (Elsevier, 2024)
Objective: To evaluate the association between inflammatory markers and abdominal fat assessed by ultrasound in prepubertal children with and without excess weight. Methods: A cross-sectional study involving 241 prepubertal children, 156 with obesity, 37 with overweight, and 48 with normal weight, aged five to ten years, who were followed at a research unit on Childhood Obesity from a teaching hospital belonging to a public health system. The concentration of interleukin-6, tumor necrosis factor-α and C-reactive protein were assessed and regression analyses, considering outcome variables such as abdominal wall and intra-abdominal fat thickness measured by ultrasound, were performed. Results: The findings highlighted an association between abdominal fat and inflammatory markers, even in children at this young age group. Subcutaneous fat showed a stronger association with inflammatory biomarkers compared to intra-abdominal fat when performing logistic regression, with a positive association between tumor necrosis factor-α and abdominal wall thickness equal to or greater than the 75th percentile in adjusted logistic regression (OR: 18.12; CI 95 %: 1.57: 209.55). Conclusions: Abdominal wall fat, in contrast to what is often observed in adults, appears to have a greater impact on chronic inflammation related to excessive weight in very young children.